2012
DOI: 10.1007/s00276-012-0960-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of the vertebral and basilar arteries in the Chinese population provides greater diagnostic accuracy of vertebrobasilar dolichoectasia and reveals gender differences

Abstract: There are significant gender differences in the diameter of both the VA and BA, indicating that gender needs to be considered in the diagnosis of VBD. These results also provide much needed quantitative data for the diagnosis of VBD in Chinese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…Diagnosis of VBD usually relies on assessment of the patient's vascular images by clinicians and radiologists based on their practical experience, in combination with clinical symptoms. A general consensus agrees that in VBD, the affected vertebrobasilar arteries are longer and broader than normal 6, 54.…”
Section: Imaging Featuresmentioning
confidence: 72%
“…Diagnosis of VBD usually relies on assessment of the patient's vascular images by clinicians and radiologists based on their practical experience, in combination with clinical symptoms. A general consensus agrees that in VBD, the affected vertebrobasilar arteries are longer and broader than normal 6, 54.…”
Section: Imaging Featuresmentioning
confidence: 72%
“…Currently, the diagnostic criteria for BADE used in China are derived from non-Asian populations 13 . Deng et al 12 previously proposed diagnostic criteria for BA ectasia for Chinese population; that is, males with a BA diameter >4.2 mm and females with a BA diameter >4.0 mm should be diagnosed with BA ectasia. The possible racial and gender differences in BA diameter may explain why there were so few patients with simple BA ectasia or BADE in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the infarct sites of BADE patients are mainly in the pons, especially in the paramedian pontine 5,[9][10][11] . Furthermore, in Chinese population, few patients were diagnosed with BA ectasia or BADE based on the current diagnostic criteria for BADE 12,13 . But there are many cases with a simply elongated BA that cannot be classified as BADE.…”
mentioning
confidence: 99%
“…Statistical differences in VA diameter between genders were not observed. However, Deng et al [9] reported the opposite relation for the Chinese population in which males exhibited a significantly wider arterial lumen compared to that of females.…”
Section: The Length and Diameter Of The Vmentioning
confidence: 97%